Satiety-Responsive Neurons in the Medial Orbitofrontal Cortex of the Macaque. - Pritchard, Thomas C.; Nedderman, Erin N.; Edwards, Erin M.; Petticoffer, Andrew C.; Schwartz, Gary J.; Scott, Thomas R. (Behavioral Neuroscience, 2008)
Feeding-related gustatory, olfactory, and visual activation of the orbitofrontal cortex (OFC) decreases following satiety. Previous neurophysiological studies have concentrated on the caudolateral OFC (clOFC). We describe satiety-induced modulation of 23 gustatory, 5 water, and 15 control neurons in the medial OFC (mOFC), where gustatory neurons represent a much larger percentage of the population. For 15 of the 23 gustatory neurons (65%), every significant taste response evoked during pre-satiety testing decreased following satiety (X = 70%). Responses evoked by the ineffective taste stimuli during pre-satiety testing were unchanged following satiety. The graded response decrements of the mOFC gustatory neurons stand in marked contrast to the clOFC responses, which are almost completely suppressed by satiety. Two other novel findings are reported here. First, all significant pre-satiety taste responses of four gustatory neurons increased following satiety (X =51%). Second, post-satiety emergent taste responses were observed in 7 of 15 neurons (47%) classified as non-responsive during pre-satiety testing. The presence of increased responsiveness and emergent gustatory neurons in the mOFC suggests that meal termination may require active processes as well as the passive loss of hedonic value. Reprinted by permission of the publisher.